PERBANYAKAN TANAMAN HIAS AIR TAWAR Alternanthera reinickii DAN Ludwigia sp SECARA IN VITRO GUNA MENDUKUNG AQUASCAPE - Irawan, Ruhil; Yunita, Rossa; Isma N., Media Fitri; M., Benny Diyah (JURNAL LITBANG KOTA PEKALONGAN, 2019)
Water plants are the hydrophytic plants that occupy the highest ecology in aquatic environments. Alternanthera reinickii and Ludwigia sp are freshwater ornamental plants that are in great deman d of aquascape lovers market. Plant tissue culture is a technique to grow the growing parts of plants, either in the form of cells, tissues or organs in aseptic conditions in vitro. The study was conducted on 15 January to 15 April 2018, at the Center for Biotechnology Research and Bogor Agricultural Genetic Resources. This research is done by using experiment method in laboratory. From the results of research on ornamental plants Alternanthera reinickii data obtained on the leaf paremeter giving regeneration substances grow the type of BAP with a concentration of 0.3 ml / l capable of producing the largest number of leaves. In shoot height parameters obtained the highest results using Kinetin treatment concentration 0.1 ml / l. In the parameter of shoot num ber of growth regulator substances BAP concentration of 0.5 ml / l resulted in the largest number of shoots. In the parameter of the root number of BAP treatment with the concentration of 0.3 ml / l shows the largest number of roots. In contrast to the ornamental plant Ludwigia sp BAP treatment of 0.1 ml / l concentration is able to produce the highest number of leaves In the parameters of shoot BAP treatment at low concentrations of 0.1 ml / l. on the parameters of BAP treatment buds concentration of 0.3 m l / l resulted in the largest number of shoots. In the parameter of the root number of BAP treatme nt, the concentration of 0.1 ml/l showed the highest number of roots. Keywords: Alternanthera reinickii, Ludwigia sp, Tissue culture, BAP, Kinetin